Vanha Marski – der finnische Mythos vom Marschall C.G. Mannerheim - Mrozewicz, Bolesław (Wydawnictwo Naukowe UAM, 2003)
The author of the article presents one of the most significant figures in the modern history of Finland: Marshal Carl Gustaf Mannerheim (1867-1951), the commander of the Finnish army during the three 'Finnish' wars and the president of Finland after World War II. Mannerheim has been perceived by the majority of the Finnish people as an almost mythical personage, a distinguished leader and the very symbol of Finnish independence. He managed thrice to save Finland from a political and military disaster. At the same time, Mannerheim was a controversial person in the Finnish society. On the one hand a national bero, on the other a representative of ultraconservative circles, who impeded the progressive trends within the Finnish working class. The article depicts those aspects of Mannerheim's life and of the political and military circumstances in Finland and Europę which lay the foundation for the myth of the Marshal as well as its spread the whole of Scandinavia. The complex discussion on Mannerheim, which has been led for the last forty years both in Finland and abroad, is also put into perspective.